Implications of Resolving the Crime of Persecution Based on Republic of Indonesia National Police Regulation Number 8 of 2021 Concerning Non-Criminal Handling Based on Restorative Justice - Sepriana, Gesta Dwi; Kurniati, Yeti; Hernawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Unitary State of the Republic of Indonesia is a democratic legal state based on Pancasila and the 1945 Constitution. Police Regulation Number 8 of 2021 concerning the Use of Restorative Justice in the Process of Criminal Offenses is a regulation that regulates the use of restorative justice. This study will discuss the following topics: the impact of handling criminal prosecutions through restorative justice in accordance with the Republic of Indonesia State Police Regulation Number 8 of 2021; challenges and initiatives associated with this approach; and the impact of handling criminal prosecutions in accordance with the provisions mentioned above. The use of restorative justice in stalking cases can be applied to mild, moderate and severe stalking situations if there is peace between the parties mediated by police mediators and community leaders, according to the results of studies and discussions. Investigators face several challenges, including: the reporter's demands are higher than the applicant's capabilities; the perpetrator is a recidivist who has a previous criminal history; the perpetrator and victim are less cooperative; consideration of victims is not carried out transparently; and previously there had been a conflict between the perpetrator and the victim